2002
DOI: 10.4049/jimmunol.168.5.2538
|View full text |Cite
|
Sign up to set email alerts
|

C1q Deficiency and Autoimmunity: The Effects of Genetic Background on Disease Expression

Abstract: Gene-targeted C1q-deficient mice have been shown to develop a syndrome reminiscent of human systemic lupus erythematosus with antinuclear Abs and proliferative glomerulonephritis. Initial phenotypic analysis conducted in (129 × C57BL/6) hybrid mice showed that background genes were a significant factor for the full expression of the autoimmune disease. To assess the contribution of background genes in the expression of the autoimmune phenotype, the disrupted C1qa gene was backcrossed for seven generations onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(75 citation statements)
references
References 26 publications
3
71
1
Order By: Relevance
“…Indeed, there is a prevailing belief that delayed or reduced clearance of apoptotic cells leads to the presentation of apoptotic antigen in the context of inflammatory signals, with resultant autoimmunity (9,12,13). This view is supported by studies in mice in which genetic deficiencies of any number of gene products (for example, C1q (14), the MER receptor tyrosine kinase (15), or MFG-E8 (16)) give rise both to delayed clearance of apoptotic cells and to the development of systemic autoimmune disease.…”
supporting
confidence: 48%
See 1 more Smart Citation
“…Indeed, there is a prevailing belief that delayed or reduced clearance of apoptotic cells leads to the presentation of apoptotic antigen in the context of inflammatory signals, with resultant autoimmunity (9,12,13). This view is supported by studies in mice in which genetic deficiencies of any number of gene products (for example, C1q (14), the MER receptor tyrosine kinase (15), or MFG-E8 (16)) give rise both to delayed clearance of apoptotic cells and to the development of systemic autoimmune disease.…”
supporting
confidence: 48%
“…According to current models, late apoptotic cells, which have lost membrane integrity and leak their intracellular contents, should behave like necrotic cells and induce an immune response (27). Thus, delayed or impaired clearance of apo-ptotic cells, as observed with targeted deletion of the complement protein C1q (14) or the MER receptor tyrosine kinase (15), is thought to lead to presentation of apoptotic antigen in the context of inflammatory signals, with resultant autoimmunity (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…Korb and Ahearn (10) first reported the binding of C1q to apoptotic cells. Subsequently, mice in which the C1q gene had been ablated demonstrated a defect in the kinetics of clearance of apoptotic cells, and, on certain genetic backgrounds, showed accumulation of apoptotic bodies in the kidney and susceptibility to autoimmune disorders (11,49). Miura-Shimura et al (50) recently reported that the presence of a unique insertion polymorphism upstream of the C1q gene in NZB mice leads to development of autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a group of 12 genes known to be localized in mitochondria (HSPA9B, COX8A, COX7C, AKAP1, BCKDHA, CLPP, FDX1, AMT, DBT, ATP5G3, AK2, and NME4) are identified as significant, and their expression level uniformly declines in older age. A number of age-regulated genes are also known to be involved in renal diseases, including C1QA, CCR1, LYN, PTPRC, and TNFSF13B, which all show increasing expression with age (27)(28)(29)(30)(31). The expression of TRPM6 (a transient receptor potential cation channel) negatively correlates with age, and mutations of this gene cause hypomagnesemia with secondary hypocalcemia (32).…”
Section: Analysis Of Systemic Inflammatory Response Induced By Lpsmentioning
confidence: 99%